Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Memorandum of Understanding Signing Ceremony Between Universiti Malaysia Pahang and Karlsruhe University of Applied Sciences - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
Our dual-degree venture with HsKA for undergraduate programmes in Automotive Engineering and Mechatronics Engineering is a success story which is highly regarded by the Ministry of Higher Education Malaysia and I am glad to note here that a number of Malaysian universities have also indicated their interest to benchmark the UMP-HsKA collaboration model